Including ethnic minorities in dementia research: Recommendations from a scoping review. Issue 1 (29th April 2022) - Brijnath, Bianca; Croy, Samantha; Sabates, Julieta; Thodis, Antonia; Ellis, Stephanie; de Crespigny, Fleur; Moxey, Annette; Day, Robert; Dobson, Annette; Elliott, Cerise; Etherington, Cathy; Geronimo, Mary Ann; et al.
Abstract: Introduction: Ethnicity influences dementia etiology, prognosis, and treatment, while culture shapes help‐seeking and care. Despite increasing population diversity in high‐income settlement countries, ethnic minorities remain underrepresented in dementia research. We investigated approaches to enhance the recruitment, and consistent collection and analysis of variables relevant to, ethnic minorities in dementia studies to make recommendations for consistent practice in dementia research. Methods: We did a scoping review, searching Embase, PsycINFO, Medline, CENTRAL, and CINAHL between January 1, 2010 and January 7, 2020. Dementia clinical and cohort studies that actively recruited ethnic minorities in high‐income countries were included. A steering group of experts developed criteria through which high‐quality studies were identified. Results: Sixty‐six articles were retrieved (51 observational; 15 experimental). Use of interpreters and translators (n = 17) was the most common method to facilitate participant recruitment. Race and ethnicity (n = 59) were the most common variables collected, followed by information on native language (n = 14), country of birth (n = 9), and length of time in country of settlement (n = 8). Thirty‐three studies translated or used a culturally validated instrument. Twenty‐three articles conducted subgroup analyses based on ethnicity. Six high‐quality studies facilitated inclusion through community engagement, collected information on multiple aspects of ethnic diversity, and adjusted/substratified to analyze the impact of ethnicity on dementia. Discussion: We make recommendations for consistent recruitment, collection, and reporting of variables relating to ethnic and cultural diversity in dementia research.